Strategi Peningkatan Tata Kelola Koperasi dalam Upaya Mencegah Praktik Tidak Sehat pada KSP Kopdit Pintu Air Cabang Koting - Da Gomez, Veronika Chantika; Mitan, Wilhelmina; Romario, Fransiscus De (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to find out the strategy for improving cooperative governance in an effort to prevent unhealthy practices at KSP Kopdit Pintu Air Koting Branch. To identify problems, this research uses qualitative research. The data collection techniques use observation, interviews and documentation. It can be concluded that things that cause unhealthy practices include lack of transparency and lack of accountability, lack of internal supervision, and non-compliance with rules and regulations. Efforts to improve cooperative governance to prevent unhealthy practices include transparency and accountability, member participation, formation of supervisory committees, anti-corruption policies and business ethics, and ongoing evaluation. Keywords : Improvement of Cooperative Governance, Unhealthy Practices